Identification of hemodynamically compromised regions by means of cerebral blood volume mapping utilizing computed tomography perfusion imaging. (April 2017) - Takahashi, Satoshi; Tanizaki, Yoshio; Akaji, Kazunori; Kimura, Hiroaki; Katano, Takehiro; Suzuki, Kentaro; Mochizuki, Yoichi; Shidoh, Satoka; Nakazawa, Masaki; Yoshida, Kazunari; Mihara, Ban
Highlights: CBV mapping utilizing CT perfusion imaging can identify hemodynamically compromised regions. Elevated relCBV accurately reflects the extent of compensatory vasodilatation involvement. Regions with elevated relCBV need for further evaluation to determine the need for EC-IC bypass surgery. Abstract: The aim of the study was to evaluate the potential role of computed tomography perfusion (CTP) imaging in identifying hemodynamically compromised regions in patients with occlusive cerebrovascular disease. Twelve patients diagnosed with either occlusion or severe stenosis of the internal carotid artery or the M1 portion of the middle cerebral artery underwent CTP imaging. The data was analyzed by an automated ROI-determining software. Patients were classified into two subgroups: an asymptomatic group consisting of three patients in whom perfusion pressure distal to the site of occlusion/stenosis (PPdis ) could be maintained in spite of the arterial occlusion/stenosis, and a symptomatic group consisting of nine patients in whom PPdis could not be maintained enough to avoid watershed infarction. Four CTP-related parameters were independently compared between the two groups. Significant differences were determined using a two-sample t -test. When statistically significant differences were identified, cut-off points were calculated using ROC curves. Analysis revealed statistically significant differences between the asymptomatic and symptomatic subgroups only in the measure of relCBV ( p = 0.028). Higher relCBV values were observed in the symptomatic subgroup. ROC curve analysis revealed 1.059 to be the optimal relCBV cut-off value for distinguishing between the asymptomatic and symptomatic subgroups. The data revealed that, in patients whose PPdis is maintained, relCBV remains around 1.00. Conversely, in patients whose PPdis decreased, relCBV increased. From these findings, we conclude that elevation of relCBV as observed using CTP imaging accurately reflects the extent of compensatory vasodilatation involvement and can identify hemodynamically compromised regions.